Farewell to a Prince. The Assassination of Galeazzo Maria Sforza in an Unpublished Benedictine Memorial (Studi di storia medioevale e di diplomatica - Nuova Serie, 2019)
This article analyzes a hitherto unknown account on the assassination of Galeazzo Maria Sforza, Duke of Milan, in the church of St. Stefano in Brolo, on 26th December 1476. This text, which is coeval to the events, is edited in the appendix of the article. The article analysis the manuscript in which the text is conserved, then follows a contextualisation of its contents within the networks of diplomacy and information at the court of the Sforza family, and with special emphasis on the monastery of St. Pietro in Gessate. Moreover, the article introduces the author of the text, Urbano Pagani of Milan. In the end the text is evaluated within the power-relations in Milan at the time of its writing.
Keywords: Galeazzo Maria Sforza; assassination; conspiracy; Lampugnani; Visconti; Olgiati; S. Pietro in Gessate; Congregation of St. Justina of Padua; information; public opinion; Urbano Pagani of Milano